Self-directed behavior reflects social stress in captive Asian elephants - Vilela, Sofia; Chen, Peini; Murakami, So; Tanabe, Yusuke; Yamamoto, Shinya (Frontiers in Veterinary Science, 2025)
Self-directed behaviors (SDBs), such as scratching, self-grooming, and body shaking, have been widely used as indicators of anxiety and social stress in non-human primates. However, research focused on SDB outside the primate range is still in infancy. Expanding this topic to other species can support animal welfare assessments and enhance comparative social studies. This study investigates whether SDB levels can reflect the social stress experienced in Asian elephants (Elephas maximus). Using all-occurrences and focal sampling on four captive individuals, we compared post-conflict SDB levels in victims to their baseline levels. Furthermore, changes in group composition during the study allowed us to examine whether individual baseline SDBs varied with social stress, measured as victimization rates across settings. Finally, we assessed whether there was any relation between levels of SDBs and stereotypic behavior. Results showed an increase in SDB levels in the victims after aggression compared to baselines, especially for behaviors recorded as counts. An estimated 39.8% increase in expected SDB counts was associated with the post-conflict context (E = 0.335, p = 0.024). The SDBs that differed more prominently were touch mouth, head shake, dust bathing, and trunk curled inwards (p < 0.05). Regarding baselines, two individuals increased their basal SDB levels when their rates as victims were the highest, although only one reached marginal significance. An individual who was never recorded as the recipient of aggression revealed remarkably low SDB levels. This study identified specific SDBs induced by social stress in Asian elephants and suggests SDB as a potential good indicator of their wellbeing.